Effect of Sodium Benzenesulfonate on SO42− Removal from Water by Polypyrrole-Modified Activated Carbon. (24th September 2021) - Zhang, Feng; Wang, Dong-Sheng; Yang, Fan; Li, Tian-Yu; Li, Hong-Yan; Cui, Jian-Guo
Abstract : Sodium benzenesulfonate was doped into polypyrrole-modified granular activated carbon (pyrrole-FeCl3 ·(6H2 O)-sodium benzenesulfonate-granular activated carbon; PFB-GAC) with the goal of improving the modified GAC's ability to adsorb sulfate from aqueous solutions. At a GAC dosage of 2.5 g and a pyrrole concentration of 1 mol L −1, the adsorption capacity of PFB-GAC prepared using a pyrrole:FeCl3 ·(6H2 O):sodium benzenesulfonate ratio of 1000 : 1500 : 1 reached 23.05 mg g −1, which was eight times higher than that for GAC and two times higher than that for polypyrrole-modified GAC without sodium benzenesulfonate. Adsorption was favored under acidic conditions and high initial sulfate concentrations. Doping with sodium benzenesulfonate facilitated polymerization to give polypyrrole. Sodium benzenesulfonate introduced more imino groups to the polypyrrole coating, and the N + sites improved ion exchange of Cl − and SO4 2− and increased the adsorption capacity of sulfate. Adsorption to the PFB-GAC followed pseudo-second-order kinetics. The adsorption isotherm conformed to the Langmuir model, and adsorption was exothermic. Regeneration using a weak alkali (NH3 ·H2 O), which released OH − slowly, caused less damage to the polypyrrole than using a strong alkali (NaOH) as the regeneration reagent. NH3 ·H2 O at a concentration of 12 mol L −1 (with the same OH − concentration as 2 mol L −1 NaOH) released 85% of the sorbed sulfate in the first adsorption-desorption cycle, and the adsorption capacity remained >6 mg g −1 after five adsorption-desorption cycles.